2013
DOI: 10.1144/jgs2012-108
|View full text |Cite
|
Sign up to set email alerts
|

Did lingering ice sheets moderate anoxia in the Early Palaeozoic of Libya?

Abstract: Abstract:The Hirnantian glaciation of West Gondwana produced a glacially sculpted topography, which is draped by organic-rich latest Ordovician and early Silurian 'hot shales'. Although these are the most important Early Palaeozoic source rock in North Africa, organic enrichment is distributed unevenly. For example, in Al Kufrah Basin, Libya, 'hot shales' are elusive, but outcrop analysis at the western basin demonstrates why this is the case. The topmost Mamuniyat Formation, of Hirnantian age, comprises glaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 This curve takes into account the progressive upsection loss of hummocky cross-stratification and increase in mud content, compatible with a deepening trend. Ice presence is interpreted on the basis of soft-sediment striae and/or ?dropstones and manganese oxide concretions (see Le Heron et al 2013). Anoxia is inferred on the basis of faunal preservation in the graptolite assemblage ) and on chemical parameters such as Th/U < 2 and presence of authigenic U (this study) Note that the precision is about ±5 % for clays and ±1-2 % for the other minerals.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 This curve takes into account the progressive upsection loss of hummocky cross-stratification and increase in mud content, compatible with a deepening trend. Ice presence is interpreted on the basis of soft-sediment striae and/or ?dropstones and manganese oxide concretions (see Le Heron et al 2013). Anoxia is inferred on the basis of faunal preservation in the graptolite assemblage ) and on chemical parameters such as Th/U < 2 and presence of authigenic U (this study) Note that the precision is about ±5 % for clays and ±1-2 % for the other minerals.…”
Section: Discussionmentioning
confidence: 85%
“…1). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 A detailed description of the stratigraphy and facies interpretation of the sedimentary strata of Jabal Eghei is given by Le Heron et al (2013, 2015 and is summarised briefly below. The oldest studied succession, the Hawaz Formation, composed of a cross-bedded and a Skolithos-burrowed sandstone facies association, occupies the westernmost part of the study area, although isolated outcrops have also been found near the eastern margin of the area.…”
Section: Geological Settingmentioning
confidence: 99%
“…From Le Heron et al . (). (c) Climbing‐dune cross‐stratification from the upper part of the M amuniyat F ormation north of G hat, SW L ibya (from Le Heron et al ., ).…”
Section: Stratigraphy and Sedimentology Of The Jabal Eghei Regionmentioning
confidence: 97%
“…). A detailed analysis of the facies of the Tanezzuft Formation is provided elsewhere (Le Heron et al ., ), and thus only a résumé is presented herein. Further south along the western flank of Al Kufrah Basin, near Jabal Duhūn, a thickness of about 100 m was reported (section ‘R’ of Lüning & Martin, ; Ghnia et al ., ).…”
Section: Stratigraphy and Sedimentology Of The Jabal Eghei Regionmentioning
confidence: 99%
See 1 more Smart Citation